The HMGB1 (C106A) mutation inhibits IL-10-producing CD19hiFcγRIIbhi B cell expansion by suppressing STAT3 activation in mice - Liu, Mengru; Zhou, Jingwen; Yin, Rui; Yin, Hui; Ding, Yue; Ma, Feng; Qian, Li (Frontiers in Immunology, 2022)
Regulatory B cells have important roles in inflammation and autoimmune diseases. A newly discovered subpopulation of B cells with a CD19hiFcγRIIbhi phenotype inhibits the proliferation of CD4+ T cells by secreting interleukin (IL)-10. The expansion of CD19hiFcγRIIbhi B cells in mouse spleen can be induced by lipopolysaccharide (LPS) or CpG oligodeoxynucleotide stimulation. However, the mechanism of CD19hiFcγRIIbhi B cell expansion and its role in inflammatory diseases are unclear. Here, we report that, under inflammatory conditions, the proliferation and immunosuppressive function of CD19hiFcγRIIbhi B cells were decreased in high mobility group box1 (HMGB1) C106A mutant mice, compared with wild-type mice. The HMGB1 (C106A) mutation in B cells reduced STAT3 phosphorylation, restricting the expansion and suppressive function of CD19hiFcγRIIbhi B cells. Compared with CD19hiFcγRIIbhi B cells from wild-type mice, CD19hiFcγRIIbhi B cells from Hmgb1(C106A) mice significantly reduced the survival of mice with sepsis. Recombinant HMGB1 promoted the expansion of IL-10-producing CD19hiFcγRIIbhi B cells among LPS-activated B cells in vitro. Furthermore, the percentage of CD19hiFcγRIIbhi regulatory B cells in the peripheral blood was increased in patients with sepsis, compared with healthy controls. These findings implicate HMGB1 in the expansion and immunosuppressive function of CD19hiFcγRIIbhi B cells.